Signifikansi Psikologi Islam dalam Tiga Generasi: Ibn Sina Al Ghazali dan Al-Attas - Akhmad Rofii Damyati (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
One of the distinguished significances of Islam in the sphere of knowledge is in psychology. Besides psychology can be traced directly to the holy Quran and hadis as its basis, many Muslim scholars have been in active to produce psychological works a long history of Islamic knowledge. This paper intends to elaborate the significances of Islamic psychology in three generations, i.e. the generation of falâsifah which is represented by Abû ‘AlîIbn Sînâ, the generation of Islamic theological mysticism which is represented by AbûHâmid al-Ghazâlî and the generation of contemporary Islamic thought which is represented by Syed Muhammad Naquib al-Attas. The reason that these three names are chosen as representations of Islamic psychology from three generation in here is because they have psychological works which can be considered to be similar each other; if not, theyare literally the same as can be seen in Kitâb al-Najâhof Ibn Sina which is similar to Ma‘ârij al-Quds of al-Ghazâlî and similar to The Nature of Man of al-Attas. Why their works look like the same? If we compare their other works, are there emphasizing in each generation to a special issue? If so, what are their significances over knowledge especially to the psychology? This paper will advocate to answer that above-mentioned questions.Keywords: Ibn Sînâ, al-Ghazâlî, al-Attas, Islamic Psychology, man, soul